PENINGKATAN KEMAMPUAN MENGGAMBAR BENTUK ALAM BENDA MELALUI PENGOLAHAN UNSUR VISUAL PADA MATA KULIAH GAMBAR BENTUK II - Ismawan - (Universitas Muhammadiyah Aceh, 2013)
This study departs from a problem student difficulties in drawing of natural objects. Based on that problem, posed research questions: What is the processing of visual elements of composition, proportion, lighting, objects and characters can enhance students' ability in drawing natural objects like object. The purpose of this study is to train students to have the ability to process visual elements (composition, proportion, lighting, objects and characters) so it can draw an object like object. The procedures used in Classroom Action Research study is a qualitative approach. Form cycles, performed repeatedly and sustainable (spiral cycle). Research subjects were students of Form II Fig subject while the object of research is the process of student learning through observation and work through the study documentation. The results obtained: 1) To control the composition, students should be told the rules of composition and exercise. The accuracy of the composition done by looking at the position of objects in the image area by way away-closer; 2) mastery of proportion can be done by applying the structure of objects. The difficulty of drawing parts of objects that is proportional resolved by giving the task of drawing objects outside of lectures and 3) the optimal use of shading to produce the impression of lighting, volume, character and a sense of material objects; 4) To draw the object in a similar need to control visual elements, observe carefully shapes and characteristic sof objects.Â Keywords: processing, visual elements, drawing shapes